Irritable bowel syndrome, endometriosis and polycystic ovary syndrome: is there a link? - Ramji, Ashwath Narayan (International Journal of Research in Medical Sciences, 2019)
Chronic pelvic pain is a common yet difficult problem to manage, plaguing the gynecologist as well as the gastroenterologist and general surgeon. Highlighted by increased visceral hypersensitivity, endometriosis and irritable bowel syndrome (IBS) are the most common causes or chronic unrelenting pelvic pain. Recently, the similarities between the two conditions has begged the question as to whether there is any common denominator between the two conditions and their likely co-existence and mismanagement. Further, the association of polycystic ovary syndrome (PCOS) in this cohort remains definitively uncharacterized. This report details a young female patient with the triad of POCS, IBS and endometriosis presenting with chronic pelvic pain.